1987
DOI: 10.1073/pnas.84.13.4557
|View full text |Cite
|
Sign up to set email alerts
|

Induction and regulation of mRNA encoding 26-kDa protein in human cell lines treated with recombinant human tumor necrosis factor.

Abstract: A 26-kDa protein, originally described in human fibroblasts superinduced for interferon f3 (IFN-13) production, and termed IFN-f32 by other investigators, is induced by cycloheximide and by a 22-kDa, interleukin 1 (IL-1)-related factor. Although the structure and sequence of the corresponding gene show nonhomology with the IFN-f3 gene, the gene is identical to that of B-cell stimulatory factor 2, a human interleukin, and displays a very potent growth and differentiation factor activity for B lymphocytes. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
1
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 36 publications
4
17
1
1
Order By: Relevance
“…One of the better studied proteins induced in many cell types by TNF is IL6. There is no correlation between sensitivity of the cell to the cytotoxic action of TNF and the inducibility of the IL6 gene; the IL6 gene can readily be induced not only in normal diploid fibroblasts, but also in TNF-resistant tumor cell lines, such as MG63 [141]. On the other hand, the IL6 gene cannot be induced in the very sensitive WEHI or in the human transformed cell lines BT20 or MCF7.…”
Section: Tnf a § An Antitijmor Agentmentioning
confidence: 94%
“…One of the better studied proteins induced in many cell types by TNF is IL6. There is no correlation between sensitivity of the cell to the cytotoxic action of TNF and the inducibility of the IL6 gene; the IL6 gene can readily be induced not only in normal diploid fibroblasts, but also in TNF-resistant tumor cell lines, such as MG63 [141]. On the other hand, the IL6 gene cannot be induced in the very sensitive WEHI or in the human transformed cell lines BT20 or MCF7.…”
Section: Tnf a § An Antitijmor Agentmentioning
confidence: 94%
“…The kinetics ofexpression ofNADPH oxidase activity and respiratory burst capability (as evaluated by measurement of H202 release in response to TPA) approximated that of cytochrome b-245 appearance, but were somehow delayed compared to the appearance of X-CGD transcripts. One possibility that could explain these data is the existence of other limiting cofactors, such as the flavoprotein or the cytosolic cofactor activity, whose expression has been shown to be affected by differentiation inducers (22,47 (50,51) and HeLa (52) cells, and induced expression of c-fos, c-myc (53), and IFN-/32 (54,55) in fibroblasts, do not require de novo protein synthesis. Enhancement of class I MHC gene expression by TNF was reported to be prevented by cycloheximide, but those results are difficult to interpret because no control of constitutively expressed genes was reported ( 13).…”
Section: Discussionmentioning
confidence: 99%
“…Its biological activities include induction of various cytokines. IL-1 has been shown to induce the production of granulocytemacrophage colony-stimulating factor [5][6][7][8][9][10][11][12][13], granulocyte CSF (G-CSF) [9][10][11][12] and B-cell stimulatory factor-2/interleukin-6/interferon-fl2 (IFN-~2)/26-kDa protein [14][15][16][17]. Recently it has also been reported that IL-1 can induce its own synthesis [18][19][20].…”
Section: Introductionmentioning
confidence: 99%